THE AGE OF CONCERTED CULTIVATION: A Racial Analysis of Parental Repertoires and Childhood Activities. (2019) - Manning, Alex
Abstract: In this paper I develop a race-centered, intersectional critique of concerted cultivation. First developed by Annette Lareau in Unequal Childhoods to describe the dominant middle-class cultural style of parenting, this powerful concept continues to shape scholarship on parenting and the social reproduction of social inequality through culture and class. I critique and reconstruct this concept based upon: 1) Existing research on racial identity and racial socialization, and racialized parenting techniques, and 2) Alternative readings of selected ethnographic material presented in Unequal Childhoods . First, I argue that concerted cultivation is a racialized parenting practice and that families negotiate and navigate a complex race- and-class-based social context of childrearing. Second, I present a re-reading of excerpts from Unequal Childhoods to show how families of color, and in particular Black families, cultivate racial knowledge and skills in their children. Third, I make a case for the larger sociological usefulness of a layered race and class analysis of parenting culture, and argue that such a framework adds more depth to core arguments made by Lareau. In the last section, I discuss the social tensions that exist within concerted cultivation and intensive parenting culture. I reflect on possible implications for normative parenting culture that matches well with neoliberal market rationality, exists within racial capitalism, but at the same time connects to anti-racist socialization and rejection of hegemonic cultural ideologies.